Mindfulness meditation modulates reward prediction errors in a passive conditioning task - Kirk, Ulrich; Montague, P. Read (Frontiers in Psychology, 2015)
Reinforcement learning models have demonstrated that phasic activity of dopamine neurons during reward expectation encodes information about the predictability of rewards and cues that predict reward. Evidence indicates that mindfulness-based approaches reduce reward anticipation signal in the striatum to negative and positive incentives suggesting the hypothesis that such training influence basic reward processing. Using a passive conditioning task and fMRI in a group of experienced mindfulness meditators and age-matched controls, we tested the hypothesis that mindfulness meditation influence reward and reward prediction error signals. We found diminished positive and negative prediction error-related blood-oxygen level-dependent (BOLD) responses in the putamen in meditators compared with controls. In the meditators, this decrease in striatal BOLD responses to reward prediction was paralleled by increased activity in posterior insula, a primary interoceptive region. Critically, responses in the putamen during early trials of the conditioning procedure (run 1) were elevated in both meditators and controls. These results provide evidence that experienced mindfulness meditators show attenuated reward prediction signals to valenced stimuli, which may be related to interoceptive processes encoded in the posterior insula.